The circle of gold : the book of time III - Prévost, Guillaume; Rodarmor, William (New York Arthur A. Levine Books, 2009)
Fourteen-year-old Sam Faulkner journeys through time to ancient China, Renaissance Rome, and into the future to rescue his friend Alicia and prevent the death of this mother.
Arthur A. Levine Books an imprint of Scholastic
Keywords: Time travel -- Fiction